Educandy-Based Media Improves Activeness and Reading Comprehension in Grade V Students: Media Berbasis Educandy Meningkatkan Aktivitas dan Pemahaman Membaca pada Siswa Kelas V - Nurbaya, Nurbaya; Paida, Andi; Ratnawati, Ratnawati (Indonesian Journal of Innovation Studies, 2025)
General Background: The integration of digital tools in elementary education has increasingly shown promise in enhancing student engagement and academic achievement. Specific Background: However, limited empirical evidence exists regarding the use of Educandy-based interactive media to improve learning outcomes in Indonesian primary schools. Knowledge Gap: There remains a need to explore how such media specifically affect student activeness and reading comprehension at the elementary level. Aims: This study investigates the effect of Educandy-based interactive learning media on the activeness and reading comprehension of fifth-grade students in Cluster V elementary schools, Patampanua District, Pinrang Regency, South Sulawesi Province. Results: Using an experimental design involving 40 students (20 experimental, 20 control), findings reveal that the experimental group showed higher mean scores in activeness (69.50 vs. 54.75) and reading comprehension (78.00 vs. 67.75). Novelty: The study provides one of the first empirical demonstrations in the region of the dual impact of Educandy media on behavioral and cognitive learning indicators in primary education. Implications: These results underscore the potential of Educandy as an effective digital pedagogical tool to enhance both engagement and comprehension, contributing to improved instructional quality in elementary schools.  Highlights: Enhances student engagement and comprehension simultaneously. Demonstrates effectiveness through controlled experimental design. Supports digital innovation in primary education settings. Keywords: Interactive Learning, Educandy Media, Student Activeness, Reading Comprehension, Elementary Education